Metabolizable energy and sulfur amino acid for laying hens in the first production cycle (Research, Society and Development, 2020)
The influence of metabolizable energy (ME) and methionine plus cystine concentration of the diet on performance the laying hens from 24 to44 weeks of age. The experimental design was completely randomized with 9 treatments in a factorial arrangement with 3 metabolizable energy levels (2755; 2900; and 3045 kcal/kg) and, 3 methionine + cystine digestible levels (0.603%; 0.670%; and 0.737%), evaluated for five periods of 28 days each. For the entire study interaction was observed (P